2012
DOI: 10.5402/2012/230621
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Development of Pectin Microsphere of Metformin Hydrochloride

Abstract: Purpose. The objective of the proposed work is to evaluate the efficacy of Pectins to qualify them as polymers for designing an oral microsphere for the delivery of selected oral antidiabetic drug-like metformin hydrochloride. Methods. Different Microspheres formulations were prepared by the water in oil (w\o) emulsion solvent evaporation technique and subsequently evaluated for its different physical parameters as well as its in vitro and in vivo drug release study. Results. The formulations F2 (98.42) and F3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…The authors reported that pectin microspheres showed better controlled release of metformin HCl compared to microspheres made of the other polymers. When the effects of metformin HCl-containing pectin microspheres and pure drug (equivalent 25 mg/kg body weight) were evaluated on diabetic rats after oral administration, it was found that microspheres continuously decreased the blood glucose level for about 5 h (from 297.5 to 173 mg/dL) compared to that of pure drug (maximum decrease obtained at 1 h, from 298.7 to 134.4 mg/dL) (Banerjee et al, 2012). Wang et al (2013) extracted a crude polysaccharide from the Mactra veneriformis (a marine clam; it is used as a seafood and also in traditional Chinese medicine).…”
Section: Metformin-loaded Microparticles and Nanoparticlesmentioning
confidence: 99%
“…The authors reported that pectin microspheres showed better controlled release of metformin HCl compared to microspheres made of the other polymers. When the effects of metformin HCl-containing pectin microspheres and pure drug (equivalent 25 mg/kg body weight) were evaluated on diabetic rats after oral administration, it was found that microspheres continuously decreased the blood glucose level for about 5 h (from 297.5 to 173 mg/dL) compared to that of pure drug (maximum decrease obtained at 1 h, from 298.7 to 134.4 mg/dL) (Banerjee et al, 2012). Wang et al (2013) extracted a crude polysaccharide from the Mactra veneriformis (a marine clam; it is used as a seafood and also in traditional Chinese medicine).…”
Section: Metformin-loaded Microparticles and Nanoparticlesmentioning
confidence: 99%
“…17 Different drug : polymer ratios were used ( Table 1). The drug (500 mg) and the gum (500, 1000, 1500 or 2000 mg) were dispersed in water.…”
Section: Formulation Of Microspheresmentioning
confidence: 99%
“…The size and distribution was adequate for optimum absorption across the mucosal layer, the stirring and speed employed in the formulation process probably accounted for the narrow range of particle sizes. 17 Representative images from the morphological studies of the polymers and microspheres by Scanning Electron Microscopy are presented in Fig. 4d-e.…”
Section: Evaluation Of the Microspheresmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24] The drugs encapsulated in chitosan microspheres include anticancer agents, anti-inflammatory agents, antibiotics, antihypertensive agents, peptide drugs, proteins, and vaccines. [26][27][28][29][30] Polymer coatings are also known to be drug carriers, providing a viable manner to avoid the risks of side effects associated with oral or parenteral therapies. [26][27][28][29][30] Polymer coatings are also known to be drug carriers, providing a viable manner to avoid the risks of side effects associated with oral or parenteral therapies.…”
Section: Introductionmentioning
confidence: 99%